(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Security is the most important thing which every living organism wants. We as a human being are much worried about our personal belongings and for that we are using models which are based on passwords and PINs. But these are easily hacked by impostors hence a fraud happens but the biometric authentication system has overcome all these drawbacks and this paper aims to give a brief review about this physiological biometric authentication techniques, along with its benefits, drawbacks, how can it be used easily and its future scope.